Merdeka Belajar Episode 6: Transformasi Dana Pemerintah untuk Pendidikan Tinggi - Reva Aditya Puteri (AGUSPATI RESEARCH INSTITUTA, 2024)
This article aims to shed light on the transformation of government funding for higher education. This study uses a descriptive qualitative method by noting because the data source was obtained by listening to oral narration from the YouTube channel of the Ministry of Education and Culture of the Republic of Indonesia entitled